Penerapan Metode Complex Proportional Assessment (COPRAS) Pada Penilaian Kelayakan Produk - Puspa Citra (Journal of Data Science and Information Systems, 2023)
Product feasibility is an important criterion that ensures the success of a product in the market. A product is considered feasible if it is able to meet customer needs and expectations, and has advantages that distinguish it from similar products. The purpose of this study is to apply the Complex Proportional Assessment (COPRAS) method in determining product feasibility in ABC UMKM. The results of recommendations between UMKM in determining product feasibility categories, there are 9 viable products with final values above 70%, and product values below 70% are product categories that are not suitable for distribution to customers.